2009
DOI: 10.1162/jocn.2008.21148
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Orbitofrontal Regions Encode Stimulus and Choice Valuation

Abstract: The weak axiom of revealed preferences suggests that the value of an object can be understood through the simple examination of choices. Although this axiom has driven economic theory, the assumption of equation between value and choice is often violated. fMRI was used to decouple the processes associated with evaluating stimuli from evaluating one's actions. Whereas activity in left posterior areas of the orbitofrontal cortex (OFC) was associated with processing the objective value of stimuli, activity in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…Instead, a number of regions showed decreasing activation as losses increased, and these regions overlapped with the regions whose activity increased for increasing gains. This finding of decreasing VMPFC activity for increasing losses has been replicated in several other studies (e.g., Cunningham et al, 2009;Plassmann et al, 2010); none of these studies have reported increased activity in regions such as insula or amygdala that are usually associated with negative outcomes.…”
Section: Value Functionsupporting
confidence: 66%
“…Instead, a number of regions showed decreasing activation as losses increased, and these regions overlapped with the regions whose activity increased for increasing gains. This finding of decreasing VMPFC activity for increasing losses has been replicated in several other studies (e.g., Cunningham et al, 2009;Plassmann et al, 2010); none of these studies have reported increased activity in regions such as insula or amygdala that are usually associated with negative outcomes.…”
Section: Value Functionsupporting
confidence: 66%
“…This provides important converging support for a growing body of neuroimaging work in healthy subjects that has reported activations within ventromedial and orbitofrontal prefrontal cortex in relation to preference judgment (Arana et al, 2003; Paulus and Frank, 2003; McClure et al, 2004; Kim et al, 2007; Chaudhry et al, 2009; Cunningham et al, 2009; Lebreton et al, 2009), and in proportion to the subjective value of stimuli in other tasks (Kringelbach et al, 2003; Plassmann et al, 2007; Kable and Glimcher, 2009; Hare et al, 2010; Peters and Buchel, 2010). …”
Section: Discussionmentioning
confidence: 59%
“…Although very discrete lesions of the OFC do not result in IGT impairments in human subjects (Manes et al, 2002), OFC-damaged patients are impaired on a different decision-making task that likewise taxes judgments involving probabilistic rewards and punishments (Rogers et al, 1999b), and neuroimaging data indicate that the OFC is recruited in such tasks (Rogers et al, 1999a;Cunningham et al, 2009;Lawrence et al, 2009;Hartstra et al, 2010). There is also an inconsistency between human data and the findings presented here, in that the performance of rats with posttraining OFC lesions matches findings from patients who had not learned the IGT before their brain injury.…”
Section: Discussionmentioning
confidence: 99%